Factors Affecting Teacher Performance At SDN Pondok Pucung 05 Bintaro (International Journal of Theory and Application in Elementary and Secondary School Education, 2022)
In recent years, SDN Pondok Pucung 05 Bintaro has experienced an alarming decline in the number of students. In fact, students who attend SDN are free of charge because the costs are paid by the government. This phenomenon reflects the problems that are happening at SDN Pondok Pucung 05 Bintaro. One of the problems that urgently and urgently needs to be addressed is the teacher's performance. Based on some literature, it is known that to improve organizational performance; a conducive organizational climate is needed–where there is full employee engagement and employee satisfaction. Therefore, the performance of teachers at SDN Pondok Pucung 05 Bintaro is thought to be influenced by several factors, such as organizational climate, job satisfaction, and teacher engagement. The purpose of this study was to determine the effect of organizational climate and job satisfaction on teacher performance mediated by teacher engagement at SDN Pondok Pucung 05 Bintaro, Indonesia. The research model used in this study is a structural model to test the proposed hypothesis using path analysis. There were 30 teachers who participated in this survey using a saturated sample. The data collection instrument used was a questionnaire distributed to 30 teachers at SDN Pondok Pucung 05 Bintaro. This study indicates that teacher performance in SDN Pondok Pucung 05 Bintaro is influenced by many factors, which organizational climate, job satisfaction, and employee engagement are important parts of the factors supporting the teacher's performance. The limitation of this study is that there are many other variables that can affect teacher performance in SDN Pondok Pucung 05 Bintaro but were not examined in this study, such as work motivation, organizational commitment, school facilities, and perceptions of public and private schools. These variables are suggested to be investigated in further research. The originality of this study shows that these results emphasize the importance of creating and managing organizational climate, job satisfaction, and employee engagement to improve teacher performance at SDN Pondok Pucung 05 Bintaro in carrying out their duties and obligations at school.